The influence of standing waves on synchronization and self-heating of Josephson junctions in resonant systems - Grib, Alexander; Seidel, Paul (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
We investigated numerically synchronization of Josephson junctions inside the transmission line. We have found that due to the resonance behavior of the system there appear the self-induced resonance steps, strong synchronization of junctions on these steps and the inhomogeneous distribution of the Joule heat extraction (the selfheating) along the line which can lead to the formation of “hot spots” in the line. The developed model can be applied to explain recent experiments in which these effects were obtained.